An unusual case of anti-neutrophilic cytoplasmic autoantibodies associated vasculitis with pauci-immune crescentic glomerulonephritis in young? Wegener’s? Churg Strauss - Pula Lakshmi, Bindumathi; Peddareddy, Spandana; Dharmapalaiah, Chethana; P., Vidyashankar; Rajagopal, Swati; Kumar K., Sunil; M. S., Girish Anand (International Journal of Research in Medical Sciences, 2022)
Anti-neutrophilic cytoplasmic autoantibodies-associated vasculitis (AAV) is very rare in India. It normally affects older population around 6th and 7th decade of life. The management of cases is also complicated. We present a case of 18 year old male patient who came with complaints of epistaxis and had hematuria and pain in the joints. He had sub conjunctival haemorrhage on presentation. On and off he had respiratory symptoms and epistaxis in the past for which he was treated as allergy and bronchial asthma. At admission he had high absolute eosinophil count and had blood 3+ positive in urine. Initially he was treated as post viral vasculitis. But patient had involvement of kidney, lung, skin, joints, eyes and on further evaluation he was found to have AAV. The case was unique due to the age of presentation and patient also had overlapping symptoms of both Wegner’s granulomatosis and Churg-Strauss syndrome.